Análise da capacidade de infiltração do pavimento intertravado de concreto - Martins, Ronaldo Miotto (2014)
The urbanization process is continuous, both in metropolis and in the smaller towns. Thus, the urban planning should be designed taking into consideration factors such as mobility and permeability of the routes by which travels over hundreds of people every day. The waterproofing of urban areas is a consequence of this urbanization. Are necessary new elements that contribute to urban drainage. The existence of sidewalks that allow infiltration of rainwater, can collaborate to minimize runoff. The interlocking concrete pavement, presents peculiar characteristics, among which those that constitute as draining floor. The study analyzes through an infiltration test, the capacity of the interlocking concrete pavement offers in relation the permeability. The test results showed unsatisfactory values for water infiltration. The regional method of execution can be one of the main causes of low efficiency.